2017
DOI: 10.1007/978-1-4939-6798-8_3
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Suboptimal Conformation Sampling for the Prediction of Protein-Peptide Interactions

Abstract: The blind identification of candidate patches of interaction on the protein surface is a difficult task that can hardly be accomplished without a heuristic or the use of simplified representations to speed up the search. The PEP-SiteFinder protocol performs a systematic blind search on the protein surface using a rigid docking procedure applied to a limited set of peptide suboptimal conformations expected to approximate satisfactorily the conformation of the peptide in interaction. All steps rely on a coarse-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Initial peptide inputs were predicted using PEP-FOLD 3, an in silico conformational prediction tool. 62,63 The output of these calculations was used as an input for 200 ns simulations of each peptide, using the CHARMM36 force field and explicit water under constant NPT conditions. The temperature was maintained at 310 K. Simulations were performed in dodecahedral unit cells with periodic boundary conditions, and charges were neutralized using sodium/chloride ions, as necessary.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…Initial peptide inputs were predicted using PEP-FOLD 3, an in silico conformational prediction tool. 62,63 The output of these calculations was used as an input for 200 ns simulations of each peptide, using the CHARMM36 force field and explicit water under constant NPT conditions. The temperature was maintained at 310 K. Simulations were performed in dodecahedral unit cells with periodic boundary conditions, and charges were neutralized using sodium/chloride ions, as necessary.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…21 Sequence alignment showed that the SBP sequence for IP 3 R2 contained an additional stretch of amino acids absent in IP 3 R1 and partly lacking in IP 3 R3 (Figure 1B). Within the putative SBP sequence of IP 3 R2, we identified a cluster of closely apposed glutamate (Glu, E) residues and delineated several candidate peptides that were tested with PEP-SiteFinder 40,41 for their interaction with a homology model of the human IP 3 R2 protein constructed with Modeller software. 42 Hereby, two peptides emerged with high interaction scores with the IP 3 -binding site of IP 3 R2: IP3RPEP5 (human) and IP3RPEP6 (mouse/rat version) (Figure 1C).…”
Section: Ip3rpep6 As a Potential Ip 3 R2 Antagonistmentioning
confidence: 99%
“…Structure prediction for CoilE peptide model with PEPFOLD3. 24,25 Live tracking of cellular dynamics using HGN-CoilR (a) HeLa cells transfected with Mito-CoilE-mEmerald were treated with 3.2 pM HGN-CoilR and irradiated using a two-photon microscope at 800 nm. Twenty-four hour post-laser-irradiated images were collected using a Leica SP8 resonant scanning confocal microscope over a period of 2.5 h to demonstrate the ability to track mitochondria movement over time.…”
Section: Confocal Imaging For Colocalization Analysismentioning
confidence: 99%